Parent soil type modulates biochar and mowing effects on soil microbial communities in karst region - Yi, Xun; Tao, Wang–Lan; Zhou, Han–Han; Zhu, Shi–Wen; Wang, Xin–Yue; Dong, Zhi–Lin; Gao, Si–Yu; Li, Xian–Kun; Song, Xu–Xin (Frontiers in Microbiology, 2025)
IntroductionKarst ecosystems are highly susceptible to degradation due to their inherent fragility and poor soil conditions. Soil microorganisms play a crucial role in nutrient cycling and ecosystem recovery. While biochar application has been shown to enhance microbial activity, its interaction with mowing–a common grassland management practice-and whether such effects vary with soil type remain unclear.MethodsA 1-year mesocosm experiment was conducted using red and calcareous soils from southwest China, with four treatments: control (CK), biochar (B), mowing (M), and combined biochar–mowing (BM). Highthroughput sequencing was used to assess microbial abundance, alpha diversity, and community structure.ResultsWe found that the individual and combined effects of biochar and mowing on soil microbial communities differed significantly between soil types. Biochar-only treatment consistently increased bacterial and fungal abundance and richness in both soil types. However, significant increases in fungal diversity, evenness and bacterial simpson were observed only in red soil. Mowing enhanced microbial abundance, richness, and diversity in red soil but had no significant effect in calcareous soil. The highest microbial abundance and richness under the combined BM treatment in red soil suggest a potential synergistic effect between biochar and mowing. Biochar significantly increased the relative abundances of dominant bacterial phyla-Proteobacteria and Actinobacteria–while decreasing Chloroflexi in red soil, with minimal changes observed in calcareous soil. Similarly, it elevated the relative abundances of fungal phyla Ascomycota and Basidiomycota, but reduced Chytridiomyota in red soil, whereas calcareous soil showed less pronounced shifts. Strong correlations were observed between soil properties and microbial community structure, particularly in red soil.ConclusionThese findings indicate that biochar and mowing can jointly improve soil microbial communities, offering potential for restoring degraded karst grasslands. However, their effectiveness is strongly mediated by parent soil type.